Burden of oral health issues and its association with the participation in ‘Health care for Newly Wedded Programme’ among reproductive aged pre-conceptive married women before their first pregnancy in Kalutara district, Sri Lanka - Hewage Dona Vindya Gayathri; Nilantha Ratnayake (College of Community Physicians of Sri Lanka, 2024)
Introduction: Oral diseases are major public health problem among reproductive aged pre-conceptive married women. 'Healthcare for Newly Wedded' programme (HNWP) address the oral health issues among them. Objective: To assess the effect of HNWP on the oral health status among reproductive aged pre-conceptive married women before their first pregnancy in Kalutara district. Methods: Community based descriptive cross-sectional study was conducted among 820 of married women before their first pregnancy in Kalutara district using an interviewer administered questionnaire and a clinical oral examination. Categorical data were presented as percentages and 95% confidence intervals (CI). Bivariate analysis was done for comparisons and multivariate analysis was done to adjust for confounders. Results: Preconceived married women carried a considerable burden of oral diseases (dental caries - 46.7%, calculus - 46.0%, gingival bleeding - 31.6%). There was a potential to reduce the presence of active dental caries by referring them to a dental clinic under the HNWP (OR = 0.443, P = 0.001). Conclusion and recommendations: Referral to a dental clinic at HNWP should be improved to improve the oral health status of this target group since the HNWP is effective in reduction of dental caries.